Why Am I So Exhausted?: Exploring Meeting-to-Work Transition Time and Recovery From Virtual Meeting Fatigue. Issue 12 (18th December 2022) - Allen, Joseph A.; Thiese, Matt S.; Eden, Emilee; Knowles, Sarah E.
Abstract : Many individuals report increased fatigue as a function of the explosion of video conferencing during the COVID-19 pandemic. This study explores individuals need to recover after meetings and how recovery is essential for overall well-being. Improving the quality of workplace meetings is primary prevention tactic for reducing worker burnout. Abstract : Objective: Ineffective meetings have been well-documented as presenting considerable direct (eg, salary) and indirect costs (eg, employee burnout). We explore the idea that people need meeting recovery, or time to transition from meetings to their next task. Doing so may reduce employee burnout. Methods: We used a quantitative survey of working adults' last meeting to determine the relationship between meeting outcomes (satisfaction and effectiveness) and meeting recovery. Results: We found that meeting outcomes are related to meeting recovery and that relationship is moderated by the degree to which the meeting was relevant to the individual. Implications for theory and practice are discussed to provide concrete recommendations for researchers, managers, and consultants. Conclusions: This study explores virtual meeting fatigue with a focus on meeting quality and explores the need for recovery after workplace meetings.